2012
DOI: 10.1088/0268-1242/27/12/125015
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of BeZnO-based UV LEDs

Abstract: Two-dimensional numerical simulation is employed to assess a number of possible design approaches aimed at optimizing the internal quantum efficiency of BeZnO-based light-emitting diodes grown along the c-axis. First, we describe the material parameters and the numerical simulation methods used to study these devices. Second, the effects of thickness, doping, and alloy composition of the BeZnO electron blocking layer are analysed in order to maximise the carrier confinement in the active region. The optimum nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Several studies have proved that, because of the poor hole mobility, for a large number of QWs at a given injection current, the QWs farther away from the cap layer are rarely filled by holes and are passive in terms of optical generation. [5,21] Actually, the optimum number of QWs is associated with the capture and escapes rates and also the well width. Holes, with poor mobility, are able to attain the wells nearer to the p-contact, but electrons with much higher mobility than the holes can penetrate to more distant wells.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have proved that, because of the poor hole mobility, for a large number of QWs at a given injection current, the QWs farther away from the cap layer are rarely filled by holes and are passive in terms of optical generation. [5,21] Actually, the optimum number of QWs is associated with the capture and escapes rates and also the well width. Holes, with poor mobility, are able to attain the wells nearer to the p-contact, but electrons with much higher mobility than the holes can penetrate to more distant wells.…”
Section: Resultsmentioning
confidence: 99%
“…[62] In order to improve the device performance of BeZnObased UV LED further, two-dimensional numerical simulation was employed to assess a number of possible design approaches aiming at optimizing the internal quantum efficiency (IQE) of BeZnO-based LED grown along the c axis. [63] For a high-efficiency operation at a wavelength of 360 nm, the effects of thickness, doping, and alloy composition of BeZnO electron blocking layer (EBL) in this heterostructure were in detail analyzed to maximize the carrier confinement in the action region. They found that if the EBL is thicker than 10 nm and has a Be molar fraction in excess of 11%; it can operate effectively as long as the doping is of p-type and at least equal to 5×10 18 cm −3 in concentration.…”
Section: Be Concentrationmentioning
confidence: 99%